A high-strength PVC composite material and preparation method thereof
Through ball milling method and silicone compound modified calcium carbonate technology, the mechanical properties and anti-aging properties of PVC composite materials are improved, and the problem of insufficient strength and impact resistance of rigid polyvinyl chloride plastics is solved.
Patent Information
- Application Number
- CN202411060702.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-05
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-08-05
AI Technical Summary
The strength and impact resistance of existing rigid polyvinyl chloride plastics are poor, and the prior art is difficult to effectively improve their mechanical properties.
The solid-phase force chemical treatment of chlorinated polyethylene and PVC resin was performed by ball milling method, and calcium carbonate was modified by homemade silicone compounds to improve the compatibility and bonding between calcium carbonate and PVC resin, and bind calcium Zinc composite stabilizer and lubricant to prepare high-strength PVC composite materials.
The mechanical properties and aging resistance of PVC composites are significantly improved, including tensile strength, impact strength and anti-aging properties.
Smart Images

Figure SMS_5 
Figure SMS_6
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polyvinyl chloride materials, and particularly relates to a high-strength PVC composite material and a preparation method thereof. Background Art
[0002] Polyvinyl chloride (PVC) has excellent chemical resistance and electrical insulation properties, and is the second largest general-purpose plastic in terms of output after polyethylene.
[0003] Polyvinyl chloride plastics are divided into two types: hard and soft. Among them, hard polyvinyl chloride plastics are often used as building pipes, medical equipment, food and beverage packaging materials, etc. The existing hard polyvinyl chloride plastics are mainly composed of polyvinyl chloride resin powder, plasticizers, stabilizers, lubricants and antioxidants. In the actual production and use process, the strength and impact resistance of hard polyvinyl chloride plastics that have not been enhanced or modified are relatively poor. In this regard, the existing technology has also made many improvements:
[0004] The invention patent with application number 201811625311.1 discloses a high-strength and low-temperature-resistant PVC composite material and its preparation method. The invention uses polyvinyl chloride resin powders with different molecular weights for compounding, and then uses different types of plasticizers to coordinate. The final prepared PVC composite material has a tensile strength of ≥24MPa, an elongation at break of ≥425%, and is resistant to low temperatures (≤-35°C).
[0005] The invention patent with application number 202010321955.2 discloses a high-toughness and high-strength PVC pipe material. The invention uses polyethylene and polyvinyl chloride for compounding, and adds the medium material chlorinated polyethylene and the compatibilizer maleic anhydride grafted polyethylene at the same time. After the optimization of the process steps such as grinding and crushing, the final prepared PVC composite material has a tensile strength of ≥59.6MPa and an impact strength (20℃) of ≥56.6kJ / m 2 , impact strength (-20℃) ≥19.6kJ / m 2 , elongation at break ≥131%.
[0006] The invention patent with application number 202310240849.5 discloses a high-strength PVC composite material and its preparation method and application. The invention uses maleic anhydride grafted polyethylene to modify polyvinyl chloride resin, and then uses perfluorooctylethyltriethoxysilane to modify calcium carbonate whiskers to improve the interface compatibility and adhesion between the modified calcium carbonate whiskers and the modified polyvinyl chloride resin, thereby improving the mechanical strength of the composite material. The impact strength of the finally prepared PVC composite material is ≥86.5kJ / m 2 , tensile strength ≥57.8MPa, transmittance ≥89.6%, transmittance after aging for 30d ≥69.4%. Summary of the invention
[0007] The purpose of the present invention is to provide a high-strength PVC composite material and a preparation method thereof, so as to improve the mechanical properties of the PVC composite material.
[0008] The purpose of the present invention can be achieved through the following technical solutions:
[0009] A high-strength PVC composite material comprises the following raw materials in parts by weight:
[0010] 100 parts of PVC resin, 10-15 parts of chlorinated polyethylene, 25-30 parts of modified calcium carbonate, 4-5 parts of calcium-zinc composite stabilizer, 3-5 parts of lubricant, 1.2-1.5 parts of PVC processing aid;
[0011] The modified calcium carbonate is prepared by the following steps:
[0012] Add calcium carbonate and siloxane compound to 50% ethanol aqueous solution, stir and react for 8-10 hours to obtain modified calcium carbonate slurry, and grind the modified calcium carbonate slurry in a grinder to a particle size D 97 ≤3.2μm. After grinding, centrifugation and drying, modified calcium carbonate is obtained.
[0013] Furthermore, the usage ratio of the 50% by mass ethanol aqueous solution, calcium carbonate and siloxane compound is 500 mL:100 g:100 g.
[0014] Furthermore, the siloxane compound is prepared by the following steps:
[0015] S1. Add vanillin, 3-chloropropyltrimethoxysilane and anhydrous aluminum chloride to ethyl acetate with stirring, introduce nitrogen protection, heat to 50-55° C., stir and reflux at constant temperature for 4-5 hours. After the reaction is completed, filter, vacuum rotary evaporate, wash and dry to obtain intermediate 1. In the preparation process of intermediate 1, the hydroxyl group in vanillin and the chlorine in 3-chloropropyltrimethoxysilane are used for substitution reaction. The reaction process is as follows:
[0016] .
[0017] S2. Add resorcinol and intermediate 1 to a 30% ethanol aqueous solution with stirring, introduce nitrogen protection, and then add a 35% hydrochloric acid aqueous solution with stirring, and the dropping time is controlled to 1 hour. After the dropwise addition is completed, the temperature is raised to 70-75°C, and the reaction is stirred at a constant temperature for 4-5 hours. After the reaction is completed, it is cooled to room temperature and filtered to obtain a solid component. The solid component is then placed in a 50% ethanol aqueous solution for recrystallization, and then filtered and dried to obtain intermediate 2. Intermediate 2 is formed by condensation of intermediate 1 and resorcinol under the action of concentrated hydrochloric acid. The reaction process is as follows:
[0018] .
[0019] S3, adding intermediate 2, acrylic acid and p-toluenesulfonic acid to toluene with stirring, heating to 80-85°C, stirring and reacting for 4-5h, after the reaction is completed, removing toluene by rotary evaporation, cooling to room temperature, washing and drying, to obtain intermediate 3, which is prepared by esterification of intermediate 2 and acrylic acid under the catalysis of p-toluenesulfonic acid, and the reaction process is as follows:
[0020] .
[0021] S4, after mixing the intermediate three, formic acid and phosphoric acid, the temperature is raised to 45-50°C, and then a 50% by mass fraction of hydrogen peroxide aqueous solution is added thereto with stirring. After the addition is completed, the temperature is raised to 65-70°C, and the reaction is stirred at a constant temperature for 8-10 hours. After the reaction is completed, the mixture is cooled to room temperature, separated, and the upper layer is washed with deionized water until neutral, and then the deionized water is removed by vacuum distillation to obtain a siloxane compound. In the above preparation process, first, in an acidic environment provided by an inorganic acid phosphoric acid, hydrogen peroxide is used to oxidize an organic acid formic acid to form a peroxy acid, and then the peroxy acid is used to oxidize the unsaturated double bond at the end of the intermediate three to achieve epoxidation and convert it into an epoxy group, thereby preparing a siloxane compound. The reaction process is as follows:
[0022] .
[0023] Furthermore, the usage ratio of ethyl acetate, vanillin, 3-chloropropyltrimethoxysilane and anhydrous aluminum chloride in S1 is 500 mL: 0.50-0.55 mol: 0.5 mol: 5-7 g.
[0024] Furthermore, the usage ratio of the 30% by mass ethanol aqueous solution, resorcinol, intermediate 1 and the 35% by mass hydrochloric acid aqueous solution in S2 is 400 mL: 0.4 mol: 79-80 g: 100 mL.
[0025] Furthermore, the usage ratio of toluene, intermediate II, acrylic acid and p-toluenesulfonic acid in S3 is 200 mL: 108-110 g: 0.1 mol: 0.8-1.0 g.
[0026] Furthermore, the usage ratio of the intermediate tris, formic acid, phosphoric acid and 50% by mass aqueous hydrogen peroxide solution in S4 is 100g:10g:0.5-1.0g:80-100g.
[0027] Furthermore, the lubricant is one of polyethylene wax and oxidized polyethylene wax.
[0028] Furthermore, the PVC processing aid is MPA102 type PVC processing aid.
[0029] Furthermore, a method for preparing a high-strength PVC composite material comprises the following steps:
[0030] Weigh each raw material according to the above-mentioned mass parts, stir and mix the PVC resin and the calcium-zinc composite stabilizer for 1 hour, then stir and add chlorinated polyethylene thereto to obtain a premix, and place the premix in a ball mill for ball milling for 1 hour, wherein the ball mill is filled with steel balls, and the total filling amount of the steel balls is 10 times the total amount of the PVC resin and the calcium-zinc composite stabilizer. Finally, the rotation speed of the ball mill is 800r / min. After the ball milling treatment is completed, a ball-milled premix is obtained, and the ball-milled premix, modified calcium carbonate, a lubricant and a PVC processing aid are mixed to obtain a mixture, and the mixture is placed in a twin-screw extruder for extrusion granulation. After the extrusion granulation is completed, it is cooled to room temperature to obtain a high-strength PVC composite material.
[0031] Furthermore, 30% of the total mass of the steel balls are steel balls with a particle size of 3 mm, 50% of the total mass of the steel balls are steel balls with a particle size of 15 mm, and 20% of the total mass of the steel balls are steel balls with a particle size of 30 mm.
[0032] Furthermore, the processing temperature of the twin-screw extruder is 200-220° C., and the screw speed of the twin-screw extruder is 300 r / min.
[0033] Beneficial effects of the present invention:
[0034] The present invention adopts a ball milling method to perform solid phase mechanical chemical treatment on chlorinated polyethylene (CPE) and PVC resin, and then adds modified calcium carbonate and other additives to finally prepare a PVC composite material. After testing, the PVC composite material prepared by the present invention has excellent mechanical properties and aging resistance. The specific analysis is as follows:
[0035] First, CPE has excellent tensile strength and impact strength. The present invention utilizes CPE to perform reinforcement treatment on PVC, and improves the interface interaction between CPE and PVC by ball milling, thereby further improving the mechanical properties of the finally prepared PVC composite material.
[0036] Then, calcium carbonate is a commonly used inorganic filler in PVC to improve the mechanical properties of PVC, but the compatibility between calcium carbonate and PVC resin is poor. Therefore, the present invention uses a homemade siloxane compound to modify calcium carbonate, and finally achieves the purpose of improving the mechanical properties of PVC composite materials by improving the compatibility between calcium carbonate and PVC resin.
[0037] Among them, the siloxane compound prepared by the present invention has abundant siloxane, epoxy group and rigid group (benzene ring). Firstly, the abundant siloxane in the siloxane compound promotes the compatibility between calcium carbonate and PVC resin through chemical adsorption and chelation, and the siloxane forms a Si-O-Si modified layer on the surface of calcium carbonate through hydrolysis and condensation, which is helpful to further improve the dispersibility and stability of the modified calcium carbonate in the PVC composite material; then, during the service process of the PVC composite material (such as the production of PVC pipes, etc.), the abundant epoxy group in the siloxane compound can capture the chloride ions generated during the degradation of PVC, thereby terminating the free radical reaction of PVC degradation. From the perspective of macroscopic performance, the addition of modified calcium carbonate can improve the anti-aging performance of the PVC composite material, and the epoxy group can form a chemical cross-linking structure after reacting with the chloride ion, which is helpful to improve the mechanical properties of the PVC composite material; finally, the abundant rigid groups in the siloxane compound can significantly improve the mechanical properties of the PVC composite material. DETAILED DESCRIPTION
[0038] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0039] Table 1 Raw material information
[0040]
[0041] Note: 30% ethanol aqueous solution, 35% hydrochloric acid aqueous solution, 50% ethanol aqueous solution, and 50% hydrogen peroxide aqueous solution were all prepared by the company's laboratory, and the raw materials were purchased from Sinopharm Chemical Reagent Co., Ltd.
[0042] Example 1
[0043] Preparation of siloxane compounds:
[0044] S1. Add 500 mL of ethyl acetate to reactor A, and then stir and add 0.50 mol of vanillin, 0.5 mol of 3-chloropropyltrimethoxysilane and 5 g of anhydrous aluminum chloride thereto, introduce nitrogen protection into reactor A, heat reactor A to 50° C., stir and reflux at constant temperature for 4 h, after the reaction is completed, filter to remove the catalyst anhydrous aluminum chloride, and then evaporate under reduced pressure to remove the solvent ethyl acetate, and then wash and dry to obtain intermediate 1;
[0045] S2, add 400mL of 30% ethanol aqueous solution to reactor B, then stir and add 0.4mol of resorcinol and 79g of intermediate 1 thereto, introduce nitrogen protection into reactor B, then stir and drop 100mL of 35% hydrochloric acid aqueous solution thereto, the dropping time is controlled within 1h, after the dropping is completed, the reactor B is heated to 70°C, stirred and reacted at constant temperature for 4h, after the reaction is completed, cooled to room temperature, filtered to obtain a solid component, the solid component is then placed in a 50% ethanol aqueous solution for recrystallization, and then filtered and dried to obtain intermediate 2;
[0046] S3, add 200 mL of toluene to the reactor C, and then stir and add 108 g of intermediate 2, 0.1 mol of acrylic acid and 0.8 g of p-toluenesulfonic acid thereto, heat the reactor C to 80°C, stir and react for 4 hours, after the reaction is completed, remove toluene by rotary evaporation, cool to room temperature, wash and dry, and obtain intermediate 3;
[0047] S4. Add 100 g of intermediate three, 10 g of formic acid and 0.5 g of phosphoric acid into reactor D with stirring. After the addition is completed, heat reactor D to 45° C., and then add 80 g of 50% by mass hydrogen peroxide aqueous solution thereto with stirring. After the addition is completed, heat reactor D to 65° C. again, stir and react at constant temperature for 8 h. After the reaction is completed, cool to room temperature, separate the liquids, take the upper layer, wash with deionized water until neutral, and then distill under reduced pressure to remove the deionized water to obtain a siloxane compound.
[0048] Example 2
[0049] Preparation of siloxane compounds:
[0050] S1. Add 500 mL of ethyl acetate to reactor A, and then stir and add 0.55 mol of vanillin, 0.5 mol of 3-chloropropyltrimethoxysilane and 6 g of anhydrous aluminum chloride thereto, introduce nitrogen protection into reactor A, heat reactor A to 55° C., stir and reflux at constant temperature for 5 h, after the reaction is completed, filter to remove the catalyst anhydrous aluminum chloride, and then evaporate under reduced pressure to remove the solvent ethyl acetate, and then wash and dry to obtain intermediate 1;
[0051] S2, add 400mL of 30% ethanol aqueous solution to reactor B, then stir and add 0.4mol of resorcinol and 80g of intermediate 1 thereto, introduce nitrogen protection into reactor B, then stir and drop 100mL of 35% hydrochloric acid aqueous solution thereto, the dropping time is controlled within 1h, after the dropping is completed, the temperature of reactor B is raised to 75°C, and the reaction is stirred at constant temperature for 5h. After the reaction is completed, cool to room temperature, filter and obtain solid component, the solid component is then placed in 50% ethanol aqueous solution for recrystallization, and then filtered and dried to obtain intermediate 2;
[0052] S3, add 200 mL of toluene to the reactor C, and then stir and add 119 g of intermediate 2, 0.1 mol of acrylic acid and 0.9 g of p-toluenesulfonic acid thereto, heat the reactor C to 85°C, stir and react for 5 hours, after the reaction is completed, remove toluene by rotary evaporation, cool to room temperature, wash and dry, and obtain intermediate 3;
[0053] S4. Add 100 g of intermediate three, 10 g of formic acid and 0.8 g of phosphoric acid into reactor D with stirring. After the addition is completed, the temperature of reactor D is raised to 50° C., and 100 g of a 50% by mass aqueous hydrogen peroxide solution is added thereto with stirring. After the addition is completed, the temperature of reactor D is raised to 70° C., and the reaction is stirred at a constant temperature for 10 hours. After the reaction is completed, the reaction is cooled to room temperature, separated, and the upper layer is washed with deionized water until neutral, and then the deionized water is removed by reduced pressure distillation to obtain a siloxane compound.
[0054] Example 3
[0055] Preparation of siloxane compounds:
[0056] S1. Add 500 mL of ethyl acetate to reactor A, and then stir and add 0.55 mol of vanillin, 0.5 mol of 3-chloropropyltrimethoxysilane and 7 g of anhydrous aluminum chloride thereto, introduce nitrogen protection into reactor A, heat reactor A to 55° C., stir and reflux at constant temperature for 4 h, after the reaction is completed, filter to remove the catalyst anhydrous aluminum chloride, and then evaporate under reduced pressure to remove the solvent ethyl acetate, and then wash and dry to obtain intermediate 1;
[0057] S2, add 400mL of 30% ethanol aqueous solution to reactor B, then stir and add 0.4mol of resorcinol and 80g of intermediate 1 thereto, introduce nitrogen protection into reactor B, then stir and drop 100mL of 35% hydrochloric acid aqueous solution thereto, the dropping time is controlled within 1h, after the dropping is completed, the temperature of reactor B is raised to 75°C, and the reaction is stirred at constant temperature for 5h. After the reaction is completed, cool to room temperature, filter and obtain solid component, the solid component is then placed in 50% ethanol aqueous solution for recrystallization, and then filtered and dried to obtain intermediate 2;
[0058] S3, add 200 mL of toluene to the reactor C, and then stir and add 110 g of intermediate 2, 0.1 mol of acrylic acid and 1.0 g of p-toluenesulfonic acid thereto, heat the reactor C to 82°C, stir and react for 5 hours, after the reaction is completed, remove toluene by rotary evaporation, cool to room temperature, wash and dry, and obtain intermediate 3;
[0059] S4. Add 100 g of intermediate three, 10 g of formic acid and 1.0 g of phosphoric acid into reactor D with stirring. After the addition is completed, heat reactor D to 48° C., and then add 100 g of 50% by mass hydrogen peroxide aqueous solution thereto with stirring. After the addition is completed, heat reactor D to 68° C. again, stir and react at constant temperature for 9 hours. After the reaction is completed, cool to room temperature, separate the liquids, take the upper layer, wash with deionized water until neutral, and then remove the deionized water by distillation under reduced pressure to obtain a siloxane compound.
[0060] Example 4
[0061] Preparation of modified calcium carbonate:
[0062] 500 mL of 50% ethanol aqueous solution was added to the reactor E, and then 100 g of calcium carbonate and 100 g of the siloxane compound prepared in Example 1 were added thereto, and the reaction was stirred for 8 h to obtain a modified calcium carbonate slurry, and the modified calcium carbonate slurry was placed in a grinder and ground to a particle size D 97 ≤3.2μm, after grinding, centrifugation and drying, modified calcium carbonate is obtained. After testing, the particle size of the calcium carbonate slurry in this embodiment is D 97 Equal to 3.2μm.
[0063] Example 5
[0064] Preparation of modified calcium carbonate:
[0065] 500 mL of 50% ethanol aqueous solution was added to the reactor E, and then 100 g of calcium carbonate and 100 g of the siloxane compound prepared in Example 2 were added thereto, and the reaction was stirred for 10 h to obtain a modified calcium carbonate slurry, and the modified calcium carbonate slurry was placed in a grinder and ground to a particle size D97 ≤3.2μm, after grinding, centrifugation and drying, modified calcium carbonate is obtained. After testing, the particle size of the calcium carbonate slurry in this embodiment is D 97 Equal to 3.0μm.
[0066] Example 6
[0067] Preparation of modified calcium carbonate:
[0068] 500 mL of 50% ethanol aqueous solution was added to the reactor E, and then 100 g of calcium carbonate and 100 g of the siloxane compound prepared in Example 3 were added thereto, and the reaction was stirred for 10 h to obtain a modified calcium carbonate slurry, and the modified calcium carbonate slurry was placed in a grinder and ground to a particle size D 97 ≤3.2μm, after grinding, centrifugation and drying, modified calcium carbonate is obtained. After testing, the particle size of the calcium carbonate slurry in this embodiment is D 97 Equal to 3.1μm.
[0069] Comparative Example 1
[0070] Comparative Example 1 is the control group of Example 5, in which the siloxane compound prepared in Example 2 in Example 5 is removed, and the remaining raw materials, raw material amounts and preparation process remain unchanged, and modified calcium carbonate is finally obtained.
[0071] Example 7
[0072] Preparation of high-strength PVC composite materials:
[0073] First, a high-strength PVC composite material includes the following raw materials by weight: 100 parts of PVC resin, 10 parts of chlorinated polyethylene, 25 parts of modified calcium carbonate prepared in Example 4, 4 parts of calcium-zinc composite stabilizer, 3 parts of polyethylene wax, and 1.2 parts of PVC processing aid;
[0074] Then, the preparation method of the high-strength PVC composite material comprises the following steps:
[0075] Weigh each raw material according to the above mass parts, stir and mix PVC resin and calcium zinc composite stabilizer for 1 hour, then stir and add chlorinated polyethylene thereto to obtain a premix, and place the premix in a ball mill for ball milling for 1 hour, wherein the ball mill is filled with steel balls, and the particle size distribution of the steel balls is 3mm30wt%+15mm50wt%+30mm20wt%, that is, 30% of the total mass of the steel balls are steel balls with a particle size of 3mm, 50% of the total mass of the steel balls are steel balls with a particle size of 15mm, and 20% of the total mass of the steel balls are steel balls with a particle size of 30mm. The total filling amount of the steel balls is The mixture is 10 times the total amount of the PVC resin and the calcium-zinc composite stabilizer. Finally, the rotation speed of the ball mill is 800 r / min. After the ball milling treatment is completed, a ball-milled premix is obtained. The ball-milled premix, the modified calcium carbonate prepared in Example 4, the polyethylene wax and the PVC processing aid are mixed to obtain a mixture. The mixture is placed in a twin-screw extruder for extrusion granulation, wherein the processing temperature of the twin-screw extruder is 200° C., and the screw speed of the twin-screw extruder is 300 r / min. After the extrusion granulation is completed, it is cooled to room temperature to obtain a high-strength PVC composite material.
[0076] Example 8
[0077] Preparation of high-strength PVC composite materials:
[0078] First, a high-strength PVC composite material includes the following raw materials by weight: 100 parts of PVC resin, 15 parts of chlorinated polyethylene, 30 parts of modified calcium carbonate prepared in Example 5, 5 parts of calcium-zinc composite stabilizer, 5 parts of oxidized polyethylene wax, and 1.5 parts of PVC processing aid;
[0079] Then, the preparation method of the high-strength PVC composite material comprises the following steps:
[0080] Weigh each raw material according to the above mass parts, stir and mix the PVC resin and the calcium-zinc composite stabilizer for 1 hour, then stir and add chlorinated polyethylene thereto to obtain a premix, and place the premix in a ball mill for ball milling for 1 hour, wherein the ball mill is filled with steel balls, and the particle size distribution of the steel balls is 3mm30wt%+15mm50wt%+30mm20wt%, that is, 30% of the total mass of the steel balls are steel balls with a particle size of 3mm, 50% of the total mass of the steel balls are steel balls with a particle size of 15mm, and 20% of the total mass of the steel balls are steel balls with a particle size of 30mm. The total filling amount of the steel balls is The mixture was placed in a twin-screw extruder for extrusion granulation, wherein the processing temperature of the twin-screw extruder was 220°C, and the screw speed of the twin-screw extruder was 300r / min. After the extrusion granulation was completed, it was cooled to room temperature to obtain a high-strength PVC composite material.
[0081] Example 9
[0082] Preparation of high-strength PVC composite materials:
[0083] First, a high-strength PVC composite material includes the following raw materials by weight: 100 parts of PVC resin, 12 parts of chlorinated polyethylene, 28 parts of modified calcium carbonate prepared in Example 6, 5 parts of calcium-zinc composite stabilizer, 5 parts of oxidized polyethylene wax, and 1.5 parts of PVC processing aid;
[0084] Then, the preparation method of the high-strength PVC composite material comprises the following steps:
[0085] Weigh each raw material according to the above mass parts, stir and mix the PVC resin and the calcium-zinc composite stabilizer for 1 hour, then stir and add chlorinated polyethylene thereto to obtain a premix, and place the premix in a ball mill for ball milling for 1 hour, wherein the ball mill is filled with steel balls, and the particle size distribution of the steel balls is 3mm30wt%+15mm50wt%+30mm20wt%, that is, 30% of the total mass of the steel balls are steel balls with a particle size of 3mm, 50% of the total mass of the steel balls are steel balls with a particle size of 15mm, and 20% of the total mass of the steel balls are steel balls with a particle size of 30mm. The total filling amount of the steel balls is 10 times the total amount of PVC resin and calcium-zinc composite stabilizer. Finally, the speed of the ball mill is 800r / min. After the ball milling treatment is completed, a ball-milled premix is obtained. The ball-milled premix, the modified calcium carbonate prepared in Example 6, the oxidized polyethylene wax and the PVC processing aid are mixed to obtain a mixture. The mixture is placed in a twin-screw extruder for extrusion granulation, wherein the processing temperature of the twin-screw extruder is 220°C, and the screw speed of the twin-screw extruder is 300r / min. After the extrusion granulation is completed, it is cooled to room temperature to obtain a high-strength PVC composite material.
[0086] Comparative Example 2
[0087] Comparative Example 2 is the control group of Example 8, in which the modified calcium carbonate prepared in Example 5 in Example 8 is replaced by the modified calcium carbonate prepared in Comparative Example 1, and the other raw materials, raw material amounts and preparation process remain unchanged, and finally a high-strength PVC composite material is obtained.
[0088] Comparative Example 3
[0089] Comparative Example 3 is the control group of Example 8, in which the modified calcium carbonate prepared in Example 5 in Example 8 is removed, and the remaining raw materials, raw material amounts and preparation process remain unchanged, and finally a high-strength PVC composite material is obtained.
[0090] Comparative Example 4
[0091] Comparative Example 4 is the control group of Example 8, in which the chlorinated polyethylene (CPE) and the PVC resin are removed by the ball milling method in Example 8 through a solid phase mechanical chemical treatment process, and the remaining raw materials, raw material amounts and preparation process remain unchanged, and finally a high-strength PVC composite material is obtained. The details are as follows:
[0092] Preparation of high-strength PVC composite materials:
[0093] First, a high-strength PVC composite material includes the following raw materials by weight: 100 parts of PVC resin, 15 parts of chlorinated polyethylene, 30 parts of modified calcium carbonate prepared in Example 5, 5 parts of calcium-zinc composite stabilizer, 5 parts of oxidized polyethylene wax, and 1.5 parts of PVC processing aid;
[0094] Then, the preparation method of the high-strength PVC composite material comprises the following steps:
[0095] The raw materials were weighed according to the above parts by mass, and PVC resin, chlorinated polyethylene, modified calcium carbonate prepared in Example 5, calcium-zinc composite stabilizer, oxidized polyethylene wax and PVC processing aid were mixed to obtain a mixture, and the mixture was placed in a twin-screw extruder for extrusion granulation, wherein the processing temperature of the twin-screw extruder was 220° C., and the screw speed of the twin-screw extruder was 300 r / min. After the extrusion granulation was completed, it was cooled to room temperature to obtain a high-strength PVC composite material.
[0096] Test Example 1
[0097] The high-strength PVC composite materials prepared in Examples 7 to 9 and Comparative Examples 2 to 4 were subjected to performance tests. The performance test process is as follows, and the test results are shown in Table 2:
[0098] a. Tensile strength (MPa): The tensile strength was tested according to the test method in GB / T 1040-92 "Test Method for Tensile Properties of Plastics". Specifically, the sample was prepared according to the Type I specimen standard to obtain a tensile specimen. The tensile strength of the tensile specimen was tested on a tensile testing machine (WD-D1; purchased from Shanghai Zhuoji Instruments Co., Ltd.) at room temperature of 25°C. The test gauge length was 25 mm and the tensile speed was 50 mm / min. Ten tensile specimens were selected for testing in a single group of embodiments / comparative examples, and the average value of the test results of the ten tensile specimens was finally taken and recorded in Table 2.
[0099] b. Bending strength (MPa): The bending strength was tested according to the test method in GB / T 9341-2000 "Test method for bending properties of plastics". Specifically, a sample with a length of 80 mm, a width of 10 mm, and a thickness of 4 mm was prepared to obtain a bending specimen. The bending strength of the bending specimen was tested on a universal testing machine (CMT6104; purchased from Shenzhen Xinsansi Material Testing Co., Ltd.) at room temperature of 25°C. The bending speed was 20 mm / min. Ten bending specimens were selected for testing in a single group of embodiments / comparative examples, and the average value of the test results of the ten bending specimens was finally taken and recorded in Table 2.
[0100] c. Impact strength (kJ / m2): The unnotched cantilever beam impact strength was tested with reference to the test method in GB / T 1843-2008 "Determination of cantilever beam impact strength of plastics". Specifically, a sample with a length of 80 mm, a width of 10 mm and a thickness of 4 mm was prepared to obtain an impact specimen. At room temperature of 25°C, the impact specimen was tested for unnotched impact strength on a cantilever beam impact testing machine (Model XJU-22; purchased from Suzhou Keshengtai Machinery Equipment Co., Ltd.). For a single group of embodiments / comparative examples, 10 impact specimens were selected for testing, and the average value of the test results of the 10 impact specimens was finally taken and recorded in Table 2.
[0101] d. Aging resistance: The aging resistance test was carried out with reference to the test method in GB / T 16422.2-2014 "Plastics Laboratory Light Source Exposure Test Method Part 2: Xenon Arc Lamp". Specifically, the xenon arc lamp was filtered by a filter, and the exposure cycle was carried out according to the standard of method A + cycle number 1 in the standard. After 500 hours of irradiation, the tensile strength, flexural strength and impact strength of the PVC composite material were tested with reference to the above test process, and recorded as: tensile strength after aging, flexural strength after aging and impact strength after aging, respectively. Finally, the average value of the test results of 10 samples was taken and recorded in Table 2.
[0102] Table 2 Performance test results
[0103] It can be seen from Table 2 that the high-strength PVC composite materials prepared in Examples 7 to 9 of the present invention have excellent mechanical properties and anti-aging properties.
[0104] It should be noted that, in this article, terms such as "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or equipment that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment.
[0105] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A high-strength PVC composite material, characterized in that: Including the following raw materials by weight: 100 parts of PVC resin, 10-15 parts of chlorinated polyethylene, 25-30 parts of modified calcium carbonate, 4-5 parts of calcium-zinc composite stabilizer, 3-5 parts of lubricant, 1.2-1.5 parts of PVC processing aid; The modified calcium carbonate is prepared by the following steps: Add calcium carbonate and siloxane compound to 50% ethanol aqueous solution, stir and react for 8-10 hours to obtain modified calcium carbonate slurry, and grind the modified calcium carbonate slurry in a grinder to a particle size D 97 ≤3.2μm, after grinding, centrifugation and drying, modified calcium carbonate is obtained; The siloxane compound is prepared by the following steps: S1. Add vanillin, 3-chloropropyltrimethoxysilane and anhydrous aluminum chloride to ethyl acetate with stirring, introduce nitrogen protection, raise the temperature to 50-55°C, stir and reflux at a constant temperature for 4-5 hours. After the reaction is completed, filter, evaporate under reduced pressure, wash and dry to obtain intermediate 1; S2, adding resorcinol and intermediate 1 to a 30% ethanol aqueous solution with stirring, introducing nitrogen protection, and then adding a 35% hydrochloric acid aqueous solution with stirring, the dropping time is controlled to 1 hour, after the dropwise addition is completed, the temperature is raised to 70-75°C, and the reaction is stirred at a constant temperature for 4-5 hours. After the reaction is completed, the reaction is cooled to room temperature, and the solid component is filtered to obtain a solid component, and the solid component is then placed in a 50% ethanol aqueous solution for recrystallization, and then filtered and dried to obtain an intermediate 2; S3, adding intermediate II, acrylic acid and p-toluenesulfonic acid to toluene with stirring, heating to 80-85° C., stirring and reacting for 4-5 hours, after the reaction is completed, removing toluene by rotary evaporation, cooling to room temperature, washing and drying, obtaining intermediate III; S4, the intermediate tris, formic acid and phosphoric acid are mixed and heated to 45-50°C, and then a 50% by mass fraction of hydrogen peroxide aqueous solution is added thereto with stirring. After the addition is completed, the temperature is raised to 65-70°C, and the mixture is stirred at a constant temperature for 8-10 hours. After the reaction is completed, the mixture is cooled to room temperature, separated, and the upper layer is washed with deionized water until it is neutral, and the deionized water is removed by vacuum distillation to obtain a siloxane compound; The preparation method of the high-strength PVC composite material comprises the following steps: Weigh each raw material according to the above-mentioned mass parts, stir and mix the PVC resin and the calcium-zinc composite stabilizer for 1 hour, then stir and add chlorinated polyethylene thereto to obtain a premix, and place the premix in a ball mill for ball milling for 1 hour, wherein the ball mill is filled with steel balls, and the total filling amount of the steel balls is 10 times the total amount of the PVC resin and the calcium-zinc composite stabilizer. Finally, the rotation speed of the ball mill is 800r / min. After the ball milling treatment is completed, a ball-milled premix is obtained, and the ball-milled premix, modified calcium carbonate, a lubricant and a PVC processing aid are mixed to obtain a mixture, and the mixture is placed in a twin-screw extruder for extrusion granulation. After the extrusion granulation is completed, it is cooled to room temperature to obtain a high-strength PVC composite material.
2. A high-strength PVC composite material according to claim 1, characterized in that: The usage ratio of ethyl acetate, vanillin, 3-chloropropyltrimethoxysilane and anhydrous aluminum chloride in S1 is 500mL:0.50-0.55mol:0.5mol:5-7g.
3. A high-strength PVC composite material according to claim 1, characterized in that: The usage ratio of the 30% by mass ethanol aqueous solution, resorcinol, intermediate 1 and the 35% by mass hydrochloric acid aqueous solution in S2 is 400 mL: 0.4 mol: 79-80 g: 100 mL.
4. The high-strength PVC composite material according to claim 1, characterized in that: The usage ratio of toluene, intermediate II, acrylic acid and p-toluenesulfonic acid in S3 is 200 mL: 108-110 g: 0.1 mol: 0.8-1.0 g.
5. The high-strength PVC composite material according to claim 1, characterized in that: The usage ratio of the intermediate tris, formic acid, phosphoric acid and 50% by mass aqueous hydrogen peroxide solution in S4 is 100g:10g:0.5-1.0g:80-100g.
6. The high-strength PVC composite material according to claim 1, characterized in that: The lubricant is one of polyethylene wax and oxidized polyethylene wax.
7. A method for preparing a high-strength PVC composite material according to any one of claims 1 to 6, characterized in that: The following steps are involved: Weigh each raw material according to the above-mentioned mass parts, stir and mix the PVC resin and the calcium-zinc composite stabilizer for 1 hour, then stir and add chlorinated polyethylene thereto to obtain a premix, and place the premix in a ball mill for ball milling for 1 hour, wherein the ball mill is filled with steel balls, and the total filling amount of the steel balls is 10 times the total amount of the PVC resin and the calcium-zinc composite stabilizer. Finally, the rotation speed of the ball mill is 800r / min. After the ball milling treatment is completed, a ball-milled premix is obtained, and the ball-milled premix, modified calcium carbonate, a lubricant and a PVC processing aid are mixed to obtain a mixture, and the mixture is placed in a twin-screw extruder for extrusion granulation. After the extrusion granulation is completed, it is cooled to room temperature to obtain a high-strength PVC composite material.
8. The method for preparing a high-strength PVC composite material according to claim 7, characterized in that: 30% of the total mass of the steel balls are steel balls with a particle size of 3 mm, 50% of the total mass of the steel balls are steel balls with a particle size of 15 mm, and 20% of the total mass of the steel balls are steel balls with a particle size of 30 mm.
9. The method for preparing a high-strength PVC composite material according to claim 7, characterized in that: The processing temperature of the twin-screw extruder is 200-220° C., and the screw speed of the twin-screw extruder is 300 r / min.
